Features of methods of physical and operational control of athlete using the «Information and diagnostic complex restoration of the functional state of an athlete» - Уткіна Олександра Геннадіївна (Oleksandra Utkina) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: the study aims to determine the possibility of using the training process athletes some parameters of heart rate variability, reflecting the physical condition of athletes before and after different size loads, as well as the recovery process in skiing. Material and Methods: control of real-time reactions of the body of an athlete and an operational range of recovery tools using the «informational diagnostic complex restoration of the functional state of an athlete». Result: to study the formation of the main components of the recovery of an athlete in skiing at different stages of sports perfection. Conclusions: the experimentally determined the optimal ratio of means and methods of recovery of an athlete at the stages of long-term preparation, as well as the peculiarities of the recovery process in some structural formations and their conjugation.